The Satisfaction Level Analysis of the SIKOJA Application’s Users in Jambi City during the COVID-19 Pandemic - Vayed, Dodi Al; Pribadi, Ulung; Fatriani, Riri Maria (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2023)
The purpose of this study was to prove the researcher's hypothesis, which was related to the satisfaction level analysis of the SIKOJA application’s users in Jambi City during the COVID-19 pandemic. Discussing the use of applications in the era of the COVID-19 pandemic. Optimal use of Information and Communication Technology resources allows the government to implement new ways of running information services to the fullest. This study used quantitative methods with data sources from questionnaires via google form with 93 respondents. Data management was carried out using SEM-pls. This study used the PICIES Framework theory to determine the factors that influenced people in using SIKOJA sensitive applications. The measured variables were performance, efficiency, information, service, and control. The results of this study indicated that the value of R square was .738, the satisfaction level of using the application was 73.8%, which the R-square identified was in the medium category. Variables that influenced users of the Jambi City SIKOJA application were performance, efficiency, information, service, and control.